Population Connectivity Predicts Vulnerability to White-Nose Syndrome in the Chilean Myotis (Myotis chiloensis)-A Genomics Approach - Thomas M. Lilley; Tiina Sävilammi; Gonzalo Ossa; Anna S. Blomberg; Anti Vasemägi; Veronica Yung; David L. J. Vendrami; Joseph S. Johnson (GENETICS SOCIETY AMERICA, 2022)
Despite its peculiar distribution, the biology of the southernmost bat species in the world, the Chilean myotis (Myotis chiloensis), has garnered little attention so far. The species has a north-south distribution of c. 2800 km, mostly on the eastern side of the Andes mountain range. Use of extended torpor occurs in the southernmost portion of the range, putting the species at risk of bat white-nose syndrome, a fungal disease responsible for massive population declines in North American bats. Here, we examined how geographic distance and topology would be reflected in the population structure of M. chiloensis along the majority of its range using a double digestion RAD-seq method. We sampled 66 individuals across the species range and discovered pronounced isolation-by-distance. Furthermore, and surprisingly, we found higher degrees of heterozygosity in the southernmost populations compared to the north. A coalescence analysis revealed that our populations may still not have reached secondary contact after the Last Glacial Maximum. As for the potential spread of pathogens, such as the fungus causing WNS, connectivity among populations was noticeably low, especially between the southern hibernatory populations in the Magallanes and Tierra del Fuego, and more northerly populations. This suggests the probability of geographic spread of the disease from the north through bat-to-bat contact to susceptible populations is low. The study presents a rare case of defined population structure in a bat species and warrants further research on the underlying factors contributing to this. See the graphical abstract here.